Implementing an Assay Detecting Anti-drug Antibody against Emicizumab: Experience from One Center in France - Auditeau, Claire; Valsecchi, Carla; Bentounes, Nûn Kalim; Le-Goff, Amandine; Harroche, Annie; Bally, Cécile; Lenting, Peter J.; Borgel, Delphine; Peyvandi, Flora; Lasne, Dominique (Thrombosis and Haemostasis, 2025)
Emicizumab is an antibody that mimics the function of factor (F)VIII and has been approved for prophylaxis in hemophilia A patients. However, the development of anti-drug antibodies (ADA) against emicizumab, although rare, can impair its efficacy. In cases with low drug levels or bleeding events, differentiating between ADA- and adherence-related issues can be challenging.We aimed at evaluating the effectiveness of a modified bridging ELISA (Valsecchi et al, JTH 2021) in detecting ADA in patients suspected of developing this response. Clinical and laboratory data were retrospectively collected from six patients with suspected ADA and one with a confirmed case. The modified ELISA was performed blindly to identify potential ADA presence. After a new ADA case was confirmed, it was characterized by assessing its expression over time and neutralizing effect.Five patients had emicizumab levels ≤1 µg/mL, while two had higher levels (13 and 15 µg/mL). Among the patients, two experienced spontaneous bleeding, and four had traumatic bleeding. ADA was detected in two patients, including the one with a known ADA. In ADA-negative patients, emicizumab levels increased following adjustments for compliance or administration issues. The newly identified ADA was neutralizing, blocking emicizumab's binding to factors IX and X. Its pattern of expression was similar to that of the known ADA case, peaking 3 months after the loss of emicizumab efficacy and remaining positive for over a year after emicizumab discontinuation.In bleeding patients with low emicizumab levels, the modified bridging ELISA may effectively differentiate ADA patients from those with other issues leading to decreased emicizumab concentration.
Keywords: hemophilia therapy; emicizumab; anti-drug antibodies; hemostasis; hemophilia A/B